The Intended and Unintended Consequences of Taxing Waste - Tommaso Colussi; Matteo Romagnoli; Elena Villar (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper investigates the economic and environmental effects of pay-as-you-throw (PAYT) waste programs. Using a newly constructed longitudinal dataset of Italian municipalities and a staked-by-event design, we obtain three main findings: (i) PAYT programs significantly reduce total waste production; (ii) they further decrease waste management costs and leave municipal finances unaffected; (iii) they generate positive spillover effects on pro-environmental behaviors not directly targeted by the program. Survey evidence suggests that PAYT increases environmental awareness and concerns of the population in treated municipalities.
Keywords: C21; H23; Q53; 330; waste management; taxation; difference-in-differences; variation in treatment timing